DFT investigation analyzed with data mining technique of rare-earth dihydrides REH2 for hydrogen storage. (21st September 2021) - Ouadah, O.; Saidi, F.; Miloudi, M.E.A.; Ziani, O.; Mahmoudi, A.; Nasr, S.
Abstract: Ab initio calculation and data mining are very useful methods to predict the interrelationships among structure properties. In this paper, the first-principles modelling based on the density functional theory (DFT) was used to explore the structural, mechanical, and electronic properties of ten hydrides REH2 (RE = La, Ce, Pr, Nd, Sm, Tb, Dy, Ho, Er, Tm). From the present work, it can be noted that LaH2, CeH2, NdH2, and PrH2 compounds crystallizing in the hydrogen-rich cubic phase present good mechanical properties which could be of use to future applications in hydrogen storage. Furthermore, the electronic structures were also evaluated to provide a deep insight regarding their trends and confirm the metallic character of these systems. While, HoH2, DyH2, ErH2, TbH2, TmH2, SmH2 hydrides are mainly hard and rigid systems with high values of the bulk modulus (B), shear modulus (G), Young's modulus (E), micro-hardness (H), and low values of B / G ratio. More significantly, the adopted principal component analysis (PCA) provided an advantageous technique in selecting and identifying the minimum of inputs variables necessary to capture all information of the systems. Highlights: A DFT investigation of mechanical and electronic properties for ten rare-earth hydrides has been performed. Elastic and mechanical properties for some dihydrides are studied. The paper explores results connected with a new approach based on data mining. LaH2, CeH2, NdH2 and PrH2 are very promising compounds for possible applications in hydrogen storage.